2021
DOI: 10.1158/1538-7755.asgcr21-101
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 101: The Tanzanian Pediatric Cancer Network: A Comprehensive Evaluation of the Incidence of Presenting Patients and Access to Pediatric Cancer Care in Tanzania

Abstract: Purpose: In sub-Saharan Africa, cancer treatment facilities are often scarce and centered in urban areas, which means many patients must travel long distances to reach cancer care. Still, little is known about how this distribution of cancer centers impacts patients' ability to access care. Methods: Records of all pediatric patients (<18yo) treated for cancer in Tanzania in 2019 through the Tanzanian Pediatric Cancer Network were reviewed. This network represents all 9 hospitals currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Pediatric cancer patients were treated in more than 4 hospitals seeking treatment while the cancer symptoms were prediagnosis, with the majority of them, referred to MNH for diagnosis confirmation and treatment, resulting in late diagnosis and treatment as most of them took more than 2 weeks to arrive at the treatment center. This finding, also shown in previous studies, showed that about 74.5% of pediatric cancer patients live more than 4 hours to reach the cancer centers [11]. This is one of the factors contributing to being late in diagnosis, delaying cancer treatment can lead to early cancer complications, and early infant mortality since most pediatric cancer patients came from disadvantaged areas.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Pediatric cancer patients were treated in more than 4 hospitals seeking treatment while the cancer symptoms were prediagnosis, with the majority of them, referred to MNH for diagnosis confirmation and treatment, resulting in late diagnosis and treatment as most of them took more than 2 weeks to arrive at the treatment center. This finding, also shown in previous studies, showed that about 74.5% of pediatric cancer patients live more than 4 hours to reach the cancer centers [11]. This is one of the factors contributing to being late in diagnosis, delaying cancer treatment can lead to early cancer complications, and early infant mortality since most pediatric cancer patients came from disadvantaged areas.…”
Section: Discussionsupporting
confidence: 80%
“…Hence if the problem is left unattended, increases long-term effects and mortality. Furthermore, most of the previous studies have been conducted to establish the prevalence, incidence, needs, and concerns of childhood cancer [3,9,11,29] They helped to expose early, late and long-term effects of cancer treatment, risk of secondary malignancies, to risk of recurrence and also they confront many issues during the treatment period [30], which include childhood deprivation and social problems. Furthermore, their experience has been associated with an increased risk of detrimental psychosocial effects impacting emotional health, socialization, educational and vocational achievement, and health care access [31].…”
Section: Currently 9 Hospitals In Tanzania Provide Cancer Therapy Inc...mentioning
confidence: 99%
See 3 more Smart Citations